Critical evaluation of different available guidelines for late‐onset hypogonadism - Vito Angelo Giagulli; Marco Castellana; Giuseppe Lisco; Vincenzo Triggiani (2020)
Abstract Background Late‐onset hypogonadism (LOH) is a syndrome characterized by clinical and biochemical evidence of low testosterone levels with advancing age. In recent years, several guidelines, position statements and other recommendations have become available. It is unclear whether similar indications are reported in these documents. Objective To review similarities and differences among available documents on the management of hypogonadism, with a special focus on LOH. Materials and methods PubMed, Google and international societies websites were searched on March 2020 for documents published in the last 10 years on the management of hypogonadism and LOH. Results Nine documents were found, each developed by: (a) the American Urological Association; (b) the British Society for Sexual Medicine; (c) the Canadian Medical Association; (d) the Endocrine Society; (e) the Endocrine Society of Australia; (f) the European Academy of Andrology; (g) the European Association of Urology; (h) the International Consultation for Sexual Medicine; and (i) the International Society for the Study of Aging Male. Discussion Despite similar principles, differences were found both for the diagnostic workup and follow‐up. Particularly, discrepancies were reported both for total and free testosterone levels for diagnosis and for total testosterone for monitoring. Conclusion Available documents differ in terms of specific recommendations for the management of hypogonadism and LOH. Given the relevant clinical implications of adequate management of these disorders, future guidelines should report more consistent measures to be adopted in clinical practice.